Potential antioxidant and hypoglycaemic effect of the flower extract of Bougainvillea spectabilis Willd. (Nyctaginaceae) - Fave Yohanna Tata,; Hafsat Ali Sa’ab,; Abdulkadir Bukar Bababe,; Muhammad Mustapha Hassan,; Wazis Chama Haruna,; Cletus Anes Ukwubile, (International Journal of Phytomedicine, 2021)
The study evaluated the antioxidant and hypoglycaemic potentials of the ethanol flower extract of Bougainvillea spectabilis. Flower extract of Bougainvillea spectabilis were obtained by cold maceration method. The preliminary phytochemical screening and hypoglycaemic effect were carried out using standard methods. Antioxidant screening was carried out using DPPH antioxidant assay test. Five rats were used for each group; normal control, standard control, 100, 200 and 400 mg/kg b.w. doses of the crude ethanol flower extract of B. spectabilis to test the hypoglycaemic effect in alloxan-induced diabetic rats. Blood glucose levels were measured at different time intervals. The preliminary phytochemical screening revealed the presence of alkaloids, saponins, strerols, terpenoids, flavonoids, and carbohydrates. The crude ethanol fraction demonstrated least antioxidant activity while the chloroform fraction showed the highest antioxidant activity followed by the hexane fraction. The ethanol flower extract showed a significant dose dependent hypoglyceamic effect after 24 hours of administration. Of the doses tested, highest hypoglycaemic effect was observed by the ethanol flower extract of the dose 400 mg/kg at 24 hours. The findings revealed that non-polar fractions have more antioxidant activity than the polar fractions while the ethanol flower extract of Bougainvillea spectabilis possesses a delayed hypoglycaemic effect.